Gaya Kepemimpinan Transformasional Dan Kompensasi Pengaruhnya Terhadap Kepuasan Kerja Karyawan Pada Pt. Istana Garmindo Jaya - Rahmat .; Syahrum Agung; Anuraga Kusumah (CV. ITTC INDONESIA, 2024)
In study with title style leadership transformational and compensatory to satisfaction Work employees , with amount samples taken totaling 75 respondents. Method used that is with instrument study distributed questionnaires to employee processed use application SPSS computer . Variable style leadership transformational (X1) and compensatory (X2) against satisfaction Work employee (Y) is processed use analysis correlation , analysis regression , t test, f test as well coefficient determination . Result of study This showing that from variable style leadership transformational (X1) effect to satisfaction work employee (Y), variable compensation (X2) has an effect to satisfaction work employee (Y), as well style leadership transformational (X1) and compensatory (X2) effects in a way together to satisfaction Work employee (Y).